Effects of oral and topical Momordica charantia-Propolis premix on wound healing - Doğan, Elif; Karademi̇r, Güler; Gedi̇kli̇, Semin; Okur, Sıtkıcan (Harran Universitesi Veteriner Fakultesi Dergisi, 2020)
Momordica charantia and Propolis (MCP) are reported to have antibacterial, antifungal, antioxidant and antiinflammatory properties. The present study determines the efficacy of the oral and topical administration of MCP onwound healing in 60 adult male rats. The wounds in the control rats were left untreated, the rats in the MCP-oral groupwere treated with oral MCP, and the animals in the MCP-topical group were treated by pouring MCP powder onto thewound. The wound size was measured on the 3rd, 7th, 14th and 21st days, and tissue specimens were taken from fiveanimals in both groups. The tissue samples were evaluated histopathologically. Remission following treatment during thefollow-up period was described as a percentage of the original wound size for each rat. A two-way ANOVA was used for theanalysis of data. The mean wound surface area was measured as 1.69 cm2. At the end of the experiment, the averagereduction was 81.40 % in MCP-topically and 87.85% in MCP-orally treated wounds. The lowest decrease in wound size wasmeasured in the control group (45.55 %). Wound size reduction was not significantly different between the MCP groups atthe end of the experiment. Re-epithelialization and neovascularization were complete in both the MCP-oral and MCPtopical groups up to day 21. Overall, the treatments with oral and topical MCP were equally effective in wound healing.MCP application can be considered for the acceleration of wound healing, in both oral and topical administrations.Keywords: Momordica charantia, Propolis, Rat, Wound healing.
Keywords: Veterinary Surgery; momordica charantia; propolis; rat; Yara iyileşmesi; Veteriner Cerrahi